Resposta :
Resposta:
Explicação passo-a-passo:
X + x2 com x = 2:
2 + 2 × 2 -> 2 + 4 = 6
Resultado = 6
Resposta:
OLÁ
[tex]x + x^{2} \\ para \: x = 2 \\ substitui \\ x + x ^{2} \\ 2 + 2^{2} \\ 2 + 4 = \\ 6 \\ espero \: ter \: ajudado[/tex]
![Ver imagem ANDREYLUCAS15399](https://pt-static.z-dn.net/files/d56/69e5def31803560b4dc7416a60e795f6.jpg)
Resposta:
Explicação passo-a-passo:
X + x2 com x = 2:
2 + 2 × 2 -> 2 + 4 = 6
Resultado = 6
Resposta:
OLÁ
[tex]x + x^{2} \\ para \: x = 2 \\ substitui \\ x + x ^{2} \\ 2 + 2^{2} \\ 2 + 4 = \\ 6 \\ espero \: ter \: ajudado[/tex]